Biological Rhythms in People from North Macedonia with Bipolar Disorder: Application of the Macedonian Biological Rhythms Interview of Assessment in Neuropsychiatry (BRIAN) - Kalcev, Goce; Barbov, Ivan; Kotevska, Pavlina Ilieska; Preti, Antonio; Carta, Mauro G. (Bentham Science Publishers Ltd., 2022)
Objective: The Biological Rhythms Interview of Assessment in Neuropsychiatry (BRIAN) is a tool aimed at clinically evaluating disturbances in biological rhythm. In this study, we examined the reliability and validity of the Macedonian version of the BRIAN. Methods: A total of 100 participants, including 50 subjects with bipolar disorder (BD) and 50 control healthy subjects, were recruited. Construct validity was tested by comparing the mean BRIAN scores of the BD patients and control subjects. Results: No difference by gender or age was noticed, but patients differed from controls in education and occupation. Reliability, as measured with Cronbach’s alpha, was good in BD individuals, except for the Rhythms subscale. Reliability in controls was less good, especially for the Sleep and Rhythms subscales. The tool was able to discriminate patients with controls, with large differences on all subscales. However, since the reliability was suboptimal for some of these subscales, these differences cannot be entirely trusted. Conclusion: The study suggests that the Macedonian version of this instrument has good psychometric characteristics and also encourages the chance of developing mixed screening tools by incorporating elements of biological rhythm dysregulation into the routine evaluation of mood.